Evolving Role of PMO in Contemporary Project Management - Kinga WĘGRECKA-CHUDZIK; Łukasz JANKOWSKI; Jerzy DUDA (Communications of International Proceedings, 2024)
The motive behind this study is to explore the evolving role of the Project Management Office (PMO) in contemporary project management, addressing the lack of comprehensive literature on PMO models and their impact on organizational performance. Despite existing studies on PMOs, there is a void in the literature concerning the detailed classification and effectiveness of various PMO models tailored to specific organizational needs. The methodology involves a comprehensive literature review and analysis of multiple PMO models, including Business Unit PMOs, Project-Specific PMOs, and Global PMOs. The study examines the functions, roles, and impact of PMOs in different organizational contexts. The findings highlight that organizations with well-established PMOs achieve higher project success rates, improved delivery, and better alignment with strategic goals. The analysis underscores the importance of aligning PMO functions with organizational culture, project complexity, and leadership support to maximize effectiveness. The study provides insights for organizations to select and implement the most suitable PMO structure, enhancing project management outcomes and overall organizational success.
Keywords: Project Management Office; Project support; Deliverables; Project Centre of Excellence; Project Portfolio.